Weaving a tapestry of colours - contributions to community & country - honouring women of African heritage in Guyana today : a sample of outstanding African-Guyanese women from various sectors of society, in tribute to the International Year of Peoples of African Descent (The Commission GeorgetownGY, 2011)
Profiles a sample of a cross-section of contemporary Guyanese women of African heritage.
Keywords: WOMEN